2006
DOI: 10.1063/1.2163257
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen exchange kinetics of epitaxial PrBaCo2O5+δ thin films

Abstract: The oxygen exchange kinetics of thin films of the oxygen-deficient double perovskite PrBaCo2O5+δ (PBCO) have been determined by electrical conductivity relaxation (ECR) and by oxygen-isotope exchange and depth profiling (IEDP). Microstructural studies indicate that the PBCO films, prepared by pulsed laser deposition, have excellent single-crystal quality and epitaxial nature. The ECR and IEDP measurements reveal that the PBCO films have high electronic conductivity and rapid surface exchange kinetics, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
129
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(135 citation statements)
references
References 17 publications
(14 reference statements)
1
129
1
1
Order By: Relevance
“…[3][4][5] In this family of compounds, the A-site cationic ordered arrangement is favored due to the large difference in Ba 2+ and rare earth ionic radii, except ͑LaBa͒Co 2 O 5+␦ ͑LBCO͒. In LBCO, the doped bivalent Ba 2+ is not only inducing plenty of oxygen deficiency but also structurally providing the capability to achieve the smallest oxygen deficiency in this family of compounds due to the very similar ionic radii between Ba 2+ and La 3+ .…”
mentioning
confidence: 99%
“…[3][4][5] In this family of compounds, the A-site cationic ordered arrangement is favored due to the large difference in Ba 2+ and rare earth ionic radii, except ͑LaBa͒Co 2 O 5+␦ ͑LBCO͒. In LBCO, the doped bivalent Ba 2+ is not only inducing plenty of oxygen deficiency but also structurally providing the capability to achieve the smallest oxygen deficiency in this family of compounds due to the very similar ionic radii between Ba 2+ and La 3+ .…”
mentioning
confidence: 99%
“…The low temperature structural properties of these compounds have been studied in detail [4][5][6][7][8] and some data are available on their high temperature oxygen chemistry. [9][10][11][12] Recently, Streule et al 8 have measured high rates of oxygen uptake in GdBaB 2 O 5+x ͑B=Mn,Co͒ together with clear indications that the ordered vacancies are important to this process. We have also observed facile oxygen uptake in PrBaCo 2 O 5+x ͑PBCO͒ powders and determined the oxygen diffusion and surface exchange rates.…”
mentioning
confidence: 99%
“…10 Similar rapid surface exchange kinetics were observed on thin films of PBCO prepared by pulsed laser deposition. 11 In this letter, we report the low temperature transport phenomena and magnetic properties of the highly epitaxial PBCO thin films on single crystal ͑001͒ SrTiO 3 ͑STO͒ substrates. Two types of domains and spinglass interaction behavior in magnetoresistance studies were found in the highly epitaxial PBCO thin films.…”
mentioning
confidence: 99%
See 2 more Smart Citations